PROFITABILITY IMPLICATIONS OF ESG CONTROVERSY MANAGEMENT UNDER FINANCIAL OPACITY IN INDONESIA - Sastroredjo, Probowo; Suganda, Tarsisius; Halim, Dorothy (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2026)
ESG controversies threaten firms’ legitimacy and stakeholder trust; however, evidence on their financial impact and the role of financial opacity remains limited. This study aims at examining whether ESG controversy management enhances financial performance in emerging markets and whether this relationship is conditioned by financial opacity. Using panel data of Indonesian listed firms from 2011 to 2023 and Refinitiv’s ESGC score, where higher values indicate stronger capabilities to address sustainability incidents, the study is grounded in legitimacy theory, stakeholder theory, and the dynamic capability perspective. The multi-method approach includes firm-, year-, and industry-fixed effects, entropy balancing, propensity score matching, and the Heckman two-stage model, while controlling for firm size, leverage, growth opportunities, and audit quality. The results show that effective ESGC management improves profitability, but the effect weakens in financially opaque firms, with implications for ESG oversight and disclosure.